Еволюція планувальних рішень малометражних квартир на прикладі Львова - Сільник, Олександра; Гнат, Галина; Silnyk, Oleksandra; Hnat, Halyna (Видавництво Львівської політехніки, 2022)
Стаття присвячена дослідженню еволюції планувальних рішень малометражних квартир із середини XVII ст. і до сьогодні у житлових будинках Львова. Описано особливості й закономірності розвитку об’ємно-просторових структур компактних помешкань. Обґрунтовано доцільність дослідження компактного житла у середовищі історичного населеного пункту та актуальність використання житлового простору у сучаних умовах.

Housing, as the basis for the formation and life of a family, is one of the main indicators of the socioeconomic state of society. Designing compact small-sized apartments makes it possible to provide the optimal number of families with comfortable housing in a short time. On the territory of Lviv, you can track the features of the development of apartments that had a compact size and were accessible to most. As a result of the study, it is possible to see the relationship between socio-cultural-economic space with the peculiarities of housing planning and its regularities. To determine the specifics of the development of compact housing on the territory of Lviv, several factors that influenced planning were identified: socio-political, economic, engineering and design and planning. The analysis of the premises of Lviv stone houses built in the late XVII – early XVIII centuries shows interesting dynamics in architectural and planning solutions. Favourable demographic, economic and political prerequisites in the nineteenth century positively affected the quantitative and qualitative state of urban homes, and the construction movement was significantly revived. The layout of the premises continues to be improved by the authors of the projects, who are already graduates of the Lviv school of architecture. At the beginning of the twentieth century, there is a distribution of comfortable housing on the territory of the city and a concentration of affordable housing in certain areas. Houses are equipped with internal utilities, sectional planning is actively used. So, the following main directions of improvement of the planning structure of apartments took place: the layout changed from enfilade to corridor-enfilade and corridor ones; the nomenclature of additional premises within the apartments themselves increased due to the device of corridors, storerooms, bathrooms, and the area of residential rooms gradually decreased, and the total area of apartments left without changes. The next period (the first half of the twentieth century) in the life of Lviv had a Soviet character. Since that time, the designed and constructed residential buildings were focused on sectional development, consisting of small-sized apartments with several rooms from one to three. Cost-effectiveness in their planning solution was achieved by maximizing the reduction of auxiliary premises. The fifties can be considered the beginning of mass housing construction according to standard projects. By the end of the XX century, four generations of a series of standard projects were developed and put into practice, which still makes up the main housing stock of Lviv. Starting from a more than a modest level of comfort, the houses of the first half of the twentieth century corresponded to the limited economic opportunities of the state of that period. In the layout of apartments, the passage of rooms again appeared, and the area of additional premises decreased, but most families already had the opportunity to get separate housing. In the early seventies, projects of a different generation were put into operation, which provided for a significant increase in the estimated area per person. Passageways were no longer allowed, the area of rooms increased by several percent, and the area of additional non-residential premises – corridors, kitchens, storerooms, etc. – also increased in apartments. The compactness of housing for the period of the late twentieth century in the post-Soviet period in Lviv has become a very relevant issue. Such premises are interesting both for temporary residents of the city – tourists and students and for indigenous Lviv residents who do not have a large families. For compact modern apartments, some opportunities change the functional space and improve the quality of the layout, which is achieved thanks to modern technological capabilities. Functional furniture and sliding partitions, complete electrical equipment for kitchens, modern equipment for sanitary and hygienic premises, and various types of built-in and transformed furniture are necessary elements of a modern apartment when applying various methods of planning and transforming its internal space. The analysis highlights the pattern of influence of socio-economic factors on compact housing. Demand has not changed over the years, on the contrary – small-sized housing has become particularly important in the central part of Lviv. Technological capabilities and the presence of a local architectural school have had a positive impact on the layout and quality of small premises. Compact apartments today provoke a wide range of interesting design and technological solutions in their minimal scale. Thanks to the creative search, the premises that have remained on the territory of Lviv since the XVII-XIX centuries continue to be in demand and appreciated. As a result of interesting planning and design solutions, inconveniences associated with the specifics of solving enfilade premises are not only cancelled, but also become the highlights of interior solutions with elements of authenticity. The study confirms the importance of small-sized housing in an urbanized environment and proves the importance of the existence of established housing infrastructure for many generations for the modern housing base of the city.
Trends in the design and building of lviv in the XIX-early XX century
Keywords: малометражне житло; компактне житло; історична забудова; архітектурно-планувальне рішення; забудова радянського періоду; пострадянський житловий простір; житлові приміщення; планувальна структура; корисна п; short-lived housing; compact housing; historical buildings; architectural-planning decision; buildings of the Soviet period; post-Soviet living space; living quarters; planning structure; usable area; 72.03; 725 (477.83)